ANALISIS IMPLEMENTASI KURIKULUM 2013 DALAM PROSES PEMBELAJARAN PADA PROGRAM KEAHLIAN AKUNTANSI DAN KEUANGAN DI SMK KOTA PEKANBARU - Ilham, Rahmad; Gimin, Gimin; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to know the implementation of the curriculum 2013 and the problems experienced by teachers in implementation of the curriculum 2013 on vocational high schools in Pekanbaru. The subject of this research wass the entire teachers who teach at the accounting and financial expertise on vocational high schools in Pekanbaru with the number of teachers was 22 from 14 schools. The data was collected by using the questionnaire. Data analysis used qualitative and quantitative method. The results showed; from 22 respondents who implement the curriculum 2013, 38.95% respondents stated that they were very good in implementation of the curriculum 2013 indicators. And of 47.40% respondents stated that they were good in implementation of the curriculum 2013 indicators. If the respond “very good” and “good” were combined it will be 86.35%. In conclusion, the implementation of the curriculum 2013 on vocational high schools in Pekanbaru is good. The problems which are still experienced by teachers in the implementation of the curriculum 2013 are (1) it is still less of students’ handbook. (2) students are less motivated by teachers. (3) teachers are still not able in managing the classroom (4) teachers do not have well-understanding to the students’ material (5) it is lack of Internet access provided by schools. (6) students have less interest in reading (7) it is less of time for reading in schools. (8) students are still not independence. (9) students cannot be able in scientific problem solving (10) teachers only use one resource (11) it is not only assessment of knowledge but also assessment of spiritual and skills (12) there is still some learners who are less motivated to achieve the competency.Keywords: Implementation the Curriculum 2013